Penggunaan Metode Pembelajaran Problem SolvingSebagai Strategi Pendidikan Agama KristenDalam Peningkatan Karakter Siswa Kristen - Tarore, Debby Margaret (STT Pelita Dunia, 2024)
Abstract: This study aims to determine the results of using problem solving learning methods in an effort to improve the character of SMK students. The method used in this study is qualitative and this research was carried out at the Christian Christian Vocational School of Saws, Semarang. Data were obtained through student attitude assessment tables and research instrument tables. Education plays a very important role in improving human resources. In essence, education aims to shape the character of someone who believes and fears God. Christian Religious Education is a vehicle for learning that facilitates students to know God through His works and to realize their knowledge of the Triune God through an attitude of life that refers to Christian values. The main task of a teacher is to be responsible for helping students in terms of learning, including in character education. In the teaching and learning process, it is the teacher who conveys the lesson, solves problems that occur in class, makes evaluations of student learning, both before, during and after the lesson takes place. The problem to be studied in this paper is whether problem solving learning methods can help improve student character according to the purpose of this writing. The conclusion of this paper is learning by using.